2014
DOI: 10.5089/9781484379752.001
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Capital Outflow Restrictions

Abstract: This paper examines the effectiveness of capital outflow restrictions in a sample of 37 emerging market economies during the period 1995-2010, using a panel vector autoregression approach with interaction terms. Specifically, it examines whether a tightening of outflow restrictions helps reduce net capital outflows. We find that such tightening is effective if it is supported by strong macroeconomic fundamentals or good institutions, or if existing restrictions are already fairly comprehensive. When none of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Similar conclusions are presented in IMF research. Saborowski, Weisfeld, and Yepez (2014) have shown that restrictions on the movement of capital can be effective if at least one of the following three conditions is present: strong macroeconomic fundamentals; a developed institutional environment; and the existence of an effective system of control over an extended period of time. 4.…”
Section: Disclosure Statementmentioning
confidence: 99%
“…Similar conclusions are presented in IMF research. Saborowski, Weisfeld, and Yepez (2014) have shown that restrictions on the movement of capital can be effective if at least one of the following three conditions is present: strong macroeconomic fundamentals; a developed institutional environment; and the existence of an effective system of control over an extended period of time. 4.…”
Section: Disclosure Statementmentioning
confidence: 99%
“…5 Existing tests of the trilemma are based on testing whether the indices of (levels) of capital controls, monetary policy autonomy and exchange rate stability add to a constant (Aizenman, Chinn and Ito, 2010) or whether nominal interest rates in a country respond more to foreign interest rates in countries with more open capital accounts and less flexible exchange rates (Obstfeld, Shambaugh and Taylor, 2005) or testing comovements of asset prices with the global financial cycle (Rey, 2015). 6 Saborowski et al (2014) use panel VARs to assess the effectiveness of capital outflow restrictions in EMEs. Studies using country-specific VARs include Cardoso and Goldfajn (1998), De Gregorio et al (2000) and Baba and Kokenyne (2011).…”
mentioning
confidence: 99%
“…Finally, the effective management of cross-border capital outflows requires certain conditions. The IMF proposes three key conditions: strong macroeconomic fundamentals, effective institutions and existing comprehensive restrictions (Saborowski, Sanya, Weisfeld & Yepez, 2014). Capital outflow restriction will be effective if at least one of these three conditions is met.…”
Section: Main Conclusionmentioning
confidence: 99%